2018
DOI: 10.1111/liv.13602
|View full text |Cite
|
Sign up to set email alerts
|

Steatosis affects the sensitivity but not the specificity of non‐invasive fibrosis tests in non‐alcoholic fatty liver disease – implications for screening strategies

Abstract: See Article on Page 331

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Since 75 % (n. 300) of the studied population is composed of patients with NAFLD, an important aspect emerging from the present study is the impact of liver steatosis and high BMI on liver stiffness assessment. Several studies demonstrated that severe liver steatosis affects liver stiffness assessed by F-TE, resulting in an overestimate of fibrosis [25]. For this reason new F-TE cut-off values have been proposed in the presence of a CAP > 300 dB/m [26][27][28][29][30].…”
Section: (95 % Ci)mentioning
confidence: 99%
“…Since 75 % (n. 300) of the studied population is composed of patients with NAFLD, an important aspect emerging from the present study is the impact of liver steatosis and high BMI on liver stiffness assessment. Several studies demonstrated that severe liver steatosis affects liver stiffness assessed by F-TE, resulting in an overestimate of fibrosis [25]. For this reason new F-TE cut-off values have been proposed in the presence of a CAP > 300 dB/m [26][27][28][29][30].…”
Section: (95 % Ci)mentioning
confidence: 99%
“…2 Of note, the NFS is a low-sensitivity/high-specificity screening tool. 3 Consequently, it can confidently rule out the presence of advanced fibrosis in patients with NAFLD with a score < −1.455, but it is unable to make a reliable diagnosis of advanced fibrosis in those with a score >0.676. 3 In order to conduct a more meaningful analysis, the author should divide the study patients (n = 159) into the 3 abovementioned NFS categories and report the SYNTAX score values in these risk groups.…”
mentioning
confidence: 99%
“…3 Consequently, it can confidently rule out the presence of advanced fibrosis in patients with NAFLD with a score < −1.455, but it is unable to make a reliable diagnosis of advanced fibrosis in those with a score >0.676. 3 In order to conduct a more meaningful analysis, the author should divide the study patients (n = 159) into the 3 abovementioned NFS categories and report the SYNTAX score values in these risk groups. However, we cannot exclude that the study by Turan 1 could be underpowered to conduct such an analysis because, in general, only 5% of all screened patients fall into the high-risk category.…”
mentioning
confidence: 99%